Bongoût 3000 - Barthel, Frédéric Jésus; Bernhart, Antoine 1950-; Bolino, Pakito 1966-; Weirdo Dave; Gfeller, Meeloo 1973-; L'Homme Moderne; Meier, Marie 1974-; Dion, MissCandy; Namur, Polo de; Sury, Caroline 1964-; Vida Loco (Bongoût, 2000)
Bongoût 3000 is the first big size Bongoût collective book. Il was screen-printed at Lactina, Kehl, Germany in 2000 by Christian Gfeller, Mathieu Regad, Polo De Namur & Fred Barthel. This project was a proper mile stone in Bongoût's history. 44 pages, 125 ex, 30 x 41cm. Featuring: Frédéric Jésus Barthel, Antoine Bernhart, Pakito Bolino, Dave 2000, Meeloo Gfeller, L'Homme Moderne, Marie Meier, Miss Candy Dion, Polo de Namur, Caroline Sury, Vida Loco... (https://beuysonsale.com)
Serigraphie. - Auflage 125 Exemplare
Keywords: Graphzine